PENANAMAN NILAI-NILAI KEBERSIHAN LINGKUNGAN OLEH GURU DI MI HAYATUDDINIAH JAMBU BURUNG KECAMATAN BERUNTUNG BARU KABUPATEN BANJAR - Shalihah, Siti; Salamah, Siti (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2017)
This research proposes about the cultivating of environmental hygiene values by teachers in MI Hayatuddiniah Jambu Burung Subdistrict Beruntung Baru Banjar district.  The cultivating of environmental hygiene values by the teacher is so important and must be build early in order to become a provision to face life later in maintaining cleanliness the surrounding environment. The problems in this research are how to cultivate the environmental cleanliness values by teachers in MI Hayatuddiniah Jambu Burung and how the environmental cleanliness in MI Hayatuddiniah Jambu Burung. This study aims to determine how far the role of teachers in planting environmental cleanliness values in MI Hayatuddiniah Jambu Burung implemented. The subjects of this study are 2 teachers of IV grade and V grade and 28 students consisting of IV grade (12 people) and V grade (16 people). While the object of this research is the cultivating of environmental hygiene values by teachers at MI Hayatuddiniah Jambu Burung. In this study used data collection techniques such as observation, interviews and documentaries. By those techniques data were collected then processed through data reduction, data presentation and conclusions. The existing data are presented with qualitative descriptive analysis and take the conclusion using inductive method. The results obtained from the cultivating of environmental hygiene values in MI Hayatuddiniah Jambu Burung can be said to be effective and good, it can be seen as; exemplary, command, motivation, advice, punishment and appreciation applied by the teacher. While the state of environmental hygiene in MI Hayatuddiniah can be said well because seen from the state of the place and the state of the student. The condition of the room seen from the arrangement of clean room chairs and tables free from scratch-graffiti, the availability of trash bins on the setup class, the broom, and a blackboard that is always clean. While the state of students seen from students who always dressed in school uniform complete with attributes, wearing clothes and pants or uniform and shoes.